2015
DOI: 10.1152/ajpendo.00470.2014
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid cell TRAF3 promotes metabolic inflammation, insulin resistance, and hepatic steatosis in obesity

Abstract: R, Rui L. Myeloid cell TRAF3 promotes metabolic inflammation, insulin resistance, and hepatic steatosis in obesity. Am J Physiol Endocrinol Metab 308: E460 -E469, 2015. First published January 27, 2015; doi:10.1152/ajpendo.00470.2014.-Myeloid cells, particularly macrophages, mediate metabolic inflammation, thus promoting insulin resistance and metabolic disease progression in obesity. Numerous cytokines, toxic metabolites, damage-associated molecular patterns, and pathogen-associated molecular patterns are inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…More recent work showed that hepatocyte-specific TRAF3 deletion protects mice from insulin resistance and hepatic steatosis3738. Interestingly, analogous results were found with myeloid-specific TRAF3 deletion39. B cells have also been shown to promote inflammation in obesity-induced Type 2 diabetes40.…”
Section: Discussionmentioning
confidence: 76%
“…More recent work showed that hepatocyte-specific TRAF3 deletion protects mice from insulin resistance and hepatic steatosis3738. Interestingly, analogous results were found with myeloid-specific TRAF3 deletion39. B cells have also been shown to promote inflammation in obesity-induced Type 2 diabetes40.…”
Section: Discussionmentioning
confidence: 76%
“…198 Previous investigations have indicated that liver-specific TRAF2-KO mice exhibited attenuated diet-induced hyperglycemia compared with controls through the inactivation of glucagon signaling; however, the deficiency of TRAF2 in the liver was not sufficient to significantly influence the HFD-induced inflammatory response or insulin sensitivity. 199 Most recently, Chen et al 200 reported that TRAF3 in myeloid cells is essential for the development of metabolic disorders, as evidenced by the finding that the myeloid cell-specific deficiency of TRAF3 dramatically reduced genetic (ob/ob) or HFD-induced insulin resistance, glucose intolerance, hepatic steatosis, and obesity resulting from its powerful capacity to regulate inflammatory responses. Although TRAFs are positive regulators of IRF activation, to the best of our knowledge, there is no evidence about the involvement of IRFs in TRAF-regulated metabolic dysfunction.…”
Section: Upstream Irf Signaling In Obesity Insulin Resistance and Hmentioning
confidence: 99%
“…10 Until recently, TRAF3 was thought to be involved mainly in the regulation of the alternative, but not the canonical, NF-ÎșB pathway; However, Perez de Diego et al 5,8 recently showed that R118W-mutant TRAF3 was responsible for the impaired TLR-induced nuclear translocation of the NF-ÎșB p65 subunit in-transformed human fibroblasts. More recently, Chen et al 31 reported that myeloid TRAF3 promotes metabolic inflammation by switching from an anti-inflammatory factor to a proinflammatory one. The underlying mechanism and functional significance of TRAF3-mediated canonical NF-ÎșB signaling, however, remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%